Early Childhood Cognitive Development in Integrated Early Childhood Education Citra Bakti - Agustina Nua; Kristian Pano; Wadeltrudis Redempta Reynewa; Yulita Kristina Tai; Maria Hendriani Bedha; Arcangela Ghiriani Nari; Oktaviani Gulo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The ability to restate the concepts or principles that have been learned that is related to the ability to think. The ability to think is one of the developments of the cognitive shutter. The term cognitive comes from the word cognition which has the equivalent of knowing (knowing). Cognitive development is the stages of growth and change that occur occurs in the span of human life to understand, process information, solve problems and know something. Developmental theory is a theory that focuses on changes and developments in physical structure, behavior and mental function in various stages of life, starting from conception to near death. In the process of child development, there are six aspects where the development is very supportive of cognitive aspects in early childhood. The purpose of this study is to increase cognitive intelligence. in group B children, understand the characteristics of children in learning and can reflect on a teacher's self after doing learning. The approach of this method is to use a qualitative approach and use a quantitative approach in which it prioritizes analytical descriptive to solve concepts and also uses statistical numerical concepts.